Proteção de superfície do ionômero de vidro: uma revisão de escopo - Marçal, Daniella Mendonça (2023)
Objective: Glass Ionomer Cement (GIC) is widely used in dentistry. However, due to its pro-longed setting time and the sensitivity of the technique, it is suggested to use materials to protect the external surface of the restorations during the initial setting time. The present study carried out a scoping review to understand the effects of using surface protectors applied to Glass Ionomer Cement, and what their consequences are. Methods: Searches were conducted in the following electronic databases: EMBASE, MEDLINE (via PubMed), LILACS, SciELO, Scopus, and Web of Science, as well as using DansEasy and Google Scholar for grey literature search. No time or language limits were imposed on the searches. All review stages were independently performed by two reviewers. A bibliometric anal-ysis was also conducted to assess journals and impact factor. Results: A total of 2,105 studies were initially identified, and after excluding ineligible studies, 50 studies met all selection criteria. Of the studies found, 64% showed positive results for the application of surface protection on glass ionomer cement. In the remaining studies, the results were better for the control group without protection or there was no significant difference be-tween the groups with and without protection. Conclusion: The available evidence suggests that the use of surface protection on the GIC has a positive effect against early contact with moisture and dryness, avoiding the harmful effects of syneresis and imbibition.